Development of hybrid solar-assisted heat pump dryer for drying paddy. (May 2023) - Yahya, Muhammad; Fahmi, Hendriwan; Hasibuan, Rosdanelli; Fudholi, Ahmad
Abstract: This recent study evaluated a hybrid solar-assisted heat pump dryer (HS-AHPD) for drying paddy and its product quality. R22 is used as a working fluid in the heat pump system during the drying experiment. The HS-AHPD decreased the paddy's weight from 420 kg (31.67% db) to 370.60 kg (16.18% db) in 5.5 h with an average air temperature of 62.9 °C and an average relative humidity of 16.1% at a mass flow rate of 0.195 kg/s. The average drying rate, specific moisture extraction rate (SMER), and specific energy consumption (SEC) were 8.34 kg/s, 0.44 kg/kWh, and 4.69 kWh/kg, respectively. The HS-AHPD's average thermal efficiency and the exergy efficiency of the drying section were found up to 29.1% and 18.4%, respectively. The furnace and the solar collector contributed 19.7% and 12.9% of energy to the HS-AHPD, respectively. The improvement potential (IP) was in the range of 628.8–824.4W. The drying resulted in higher-quality products due to higher head rice yield (93.10 ± 1.044%), lower broken rice (4.41 ± 0.737%), and lower rice grouts (1.11 ± 0.271%).